Chapter Instant Architecture: Hosted Access to the Archivision Research Library with Built-In Image Management & Presentation Tools - Burns, Maureen (Proceedings e report, 2018)
The Archivision Research Library is a collection of 100,000 digital images of art and architecture professionally photographed by a trained architect. It documents the built environment--from ancient monuments to cutting-edge contemporary constructions--with extensive, standardized descriptive metadata. Archivision is accessible for research and teaching through a web-based application--a dedicated hosted instance of MDID--with vrcHost LLC delivering full services and technical support: installation, integration, and maintenance. This combination provides not only instant access to Archivision, but also to sophisticated tools for managing images using an open source media management system to discover, aggregate, study, and present digital media.